COVID-19 outcomes in MS: Observational study of early experience from NYU Multiple Sclerosis Comprehensive Care Center. Issue 5 (September 2020) - Parrotta, Erica; Kister, Ilya; Charvet, Leigh; Sammarco, Carrie; Saha, Valerie; Charlson, Robert Erik; Howard, Jonathan; Gutman, Josef Maxwell; Gottesman, Malcolm; Abou-Fayssal, Nada; Wolintz, Robyn; Keilson, Marshall; et al.
Abstract : Objective: To report outcomes on patients with multiple sclerosis (MS) and related disorders with coronavirus disease 2019 (COVID-19) illness. Methods: From March 16 to April 30, 2020, patients with MS or related disorders at NYU Langone MS Comprehensive Care Center were identified with laboratory-confirmed or suspected COVID-19. The diagnosis was established using a standardized questionnaire or by review of in-patient hospital records. Results: We identified 76 patients (55 with relapsing MS, of which 9 had pediatric onset; 17 with progressive MS; and 4 with related disorders). Thirty-seven underwent PCR testing and were confirmed positive. Of the entire group, 64 (84%) patients were on disease-modifying therapy (DMT) including anti-CD20 therapies (n = 34, 44.7%) and sphingosine-1-phosphate receptor modulators (n = 10, 13.5%). The most common COVID-19 symptoms were fever and cough, but 21.1% of patients had neurologic symptom recrudescence preceding or coinciding with the infection. A total of 18 (23.7%) were hospitalized; 8 (10.5%) had COVID-19 critical illness or related death. Features more common among those hospitalized or with critical illness or death were older age, presence of comorbidities, progressive disease, and a nonambulatory status. No DMT class was associated with an increased risk of hospitalization or fatal outcome. Conclusions: Most patients with MS with COVID-19 do not require hospitalization despite being on DMTs. Factors associated with critical illness were similar to the general at-risk patient population. DMT use did not emerge as a predictor of poor COVID-19 outcome in this preliminary sample.